2020
DOI: 10.1371/journal.pone.0233275
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic consumption study in two hospitals in Asmara from 2014 to 2018 using WHO’s defined daily dose (DDD) methodology

Abstract: This study compares the antibiotic consumption rates over a period of five years in two hospitals in Eritrea, Orotta National Referral and Teaching Hospital (ONRTH) and Hazhaz Zonal Referral Hospital (HZRH). Antibiotic consumption is an important parameter in the study of antibiotic use. However, no published data on consumption rates exist for these two hospitals, thus the aim of the study is to measure and compare a five year antibiotic consumption trends of the two hospitals' medical wards using Defined Dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…in Asmara, Eritrea. 26 However, it was inconsistent with a study by Gutema et al ., 10 who conducted a study in three medical wards of one of the largest tertiary hospitals in Ethiopia and reported that their antibiotic consumption was 91.8 DDD/100 bed-days. The higher figure obtained in this study reflects the large number of antibiotics that are being used in our hospitals.…”
Section: Discussionmentioning
confidence: 85%
“…in Asmara, Eritrea. 26 However, it was inconsistent with a study by Gutema et al ., 10 who conducted a study in three medical wards of one of the largest tertiary hospitals in Ethiopia and reported that their antibiotic consumption was 91.8 DDD/100 bed-days. The higher figure obtained in this study reflects the large number of antibiotics that are being used in our hospitals.…”
Section: Discussionmentioning
confidence: 85%
“…Patients were categorised into two groups: whether they consumed any antibiotic during follow-up or not. A standardised antibiotic consumption unit (standardised antibiotic days) was implemented to allow comparison between different antibiotic strengths and dosing regimens (17)(18)(19). Consumption ranged from 0.17 to 14 standardised antibiotic days and patients who consumed antibiotic were categorised into two categories: ≤ 3 and > 3 standardised antibiotic days.…”
Section: Data Inclusionmentioning
confidence: 99%
“…Studies have revealed that incorrect choice of antibiotics or its duration of action persists in 25% to 75% of cases [6]. It is very important to prescribe drug rationally especially in developing countries where the limited fund is available in health care and drugs [7].…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of antibiotic use is antibiotic consumption. There are several metrics of measuring antibiotic consumption [6]. One of the methods is developed and maintained by the WHO Collaborating Centre for Drug Statistics Methodology [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation